Kesenjangan Pengaturan Perlindungan Konsumen dalam Transaksi Aset Kripto melalui Platform Tidak Terdaftar di Indonesia - Ulva Kartika Dewi; Diani Sadiawati (Dinasti Research, 2026)
The development of the digital economy has driven the increasing use of crypto assets as an investment instrument in Indonesia, yet this has been accompanied by a surge in transactions through unregistered platforms or exchangers, giving rise to consumer protection issues. The digital, decentralized, and cross-border (borderless) nature of such transactions makes legal oversight difficult. This study analyzes consumer protection, business actor liability, and dispute resolution mechanisms in crypto asset transactions conducted through unregistered platforms, using a normative juridical method with statutory and conceptual approaches based on library research. The findings indicate that existing regulations have not fully accommodated the characteristics of such transactions; data from the Financial Services Authority (OJK) as of June 2026 recorded that only around 29% (IDR 196.93 billion) of the IDR 674.1 billion in secured victim funds from digital fraud had been returned, reflecting weaknesses in the loss-recovery mechanism. Business actors are obligated to provide compensation when losses arise from errors or negligence in their systems, while disputes may be resolved through internal complaints, OJK, the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK), the Consumer Dispute Resolution Body (BPSK), and litigation as a last resort. Strengthening and harmonizing regulations, along with enhanced supervision, are needed to achieve legal certainty and effective consumer protection in crypto asset transactions in Indonesia.